Implementation of Public Service Policy through Online Media and Drive Thru at the Bogor City Population and Civil Registration Office - Abdul Azis Partahian Suregar; Muhamad Husein Maruapey; R. Oetje Subagdja (Journal La Bisecoman, 2024)
The implementation of public service policies through online media is a service to facilitate the public in managing population documents. With this service, people do not need to queue at the Bogor City Disdukcapil office. This service policy is a form of application of presidential regulation number 95 of 2018 concerning online-based government systems. The purpose of this study is to determine the process of implementing service policies through online drive thru media at Disdukcapil Bogor City and the impact resulting from this policy. This research uses qualitative methods. Data was collected by interviews, observation and documentation. The data is then analyzed by data reduction, data presentation and conclusions. The results showed that the process of implementing public service policies through online drive thru at the Bogor City Disdukcapil which was seen from the dimensions of communication, resources, disposition and bureaucratic structure had been carried out well. However, there are obstacles in the communication dimension, this is because there are still quite a lot of people who do not know and do not understand about the use of services through online drive thru media. On the other hand, this policy has had a positive impact. This can be seen from the fact that there are also many people who use services through online drive thru media. The implications of research on the implementation of public service policies through the online drive-thru media Disdukcapil Bogor City are theoretically good, but the resulting impact has not been maximized.